Phenolic compounds from Pterocaulon alopecuroides - Alarcón, Silvia Rosana (2010)
Aerial parts of Pterocaulon alopecuroides (Lam.) DC. (Asteraceae), were collected at the flowering stage in December 2003 in Salta, Argentina. The identification was carried out by Ing. Julio Tolaba. A voucher specimen (n° 3399) is on deposit at the Museo de la Facultad de Ciencias Naturales, Universidad Nacional de Salta, Salta, Argentina.